Ahmad Donish's work "Risola" covers the history of the Mangit period (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Ahmad Donish Bukhari wrote "Risolai dar nazmi tamaddun va taovun" about the reform in 1870-1873 ("Culture and the order of society)". However, the emir did not like the ideas in it and removed him from the palace (1874). Ahmad Donish served as a judge in Bukhara districts for a certain period of time. After the death of Amir Muzaffar, he returned to Bukhara and taught in one of the madrasals.The 100-year rule of the Mangit dynasty was written in the work "History of the House of Mangitiya", known as "Historical Risolai".